Prevalence of Cognitive Impairment in Dialysis Patients in Gauteng Province, South Africa - Ndhlovu, Tebogo; Repsold, Lisa; Ndlovu, Kwazi; Muranda, Albert (Journal of Clinical Nephrology, 2024)
Introduction: Cognitive impairment is defined as a new deficit in at least two areas of cognitive functioning. These may include disturbances in memory, executive functioning, attention or speed of information processing, perceptual motor abilities, or language. It has been shown that cognitive impairment is associated with the severity of kidney disease. Methods: The study was a descriptive research design, with participants purposively sampled from the general chronic kidney disease population which included haemodialysis and peritoneal dialysis patients at Steve Biko Academic Hospital in Pretoria, Gauteng Province, South Africa. Hundred and fifty-one participants (76 hemodialysis & 75 peritoneal dialysis patients), 58% were males, and 42% were females aged 19-61 years. To establish the prevalence of cognitive impairment by testing the level of cognition the Mini-Mental State Examination was utilized to provide a brief screening test to quantitatively assess the cognitive abilities and cognitive changes of patients while on dialysis. Results: Ninety-nine percent (99%) of the recruited population reported no cognitive impairment, irrespective of dialysis modality, demographic characteristics, and socio-economic status. Conclusion: Despite the findings highlighting that the majority of the chronic kidney disease population at Steve Biko Academic Hospital reported no cognitive impairment, it is crucial to increase awareness of the potential effects of cognitive impairment on daily activities, quality of life, and treatment adherence. Early detection and management of cognitive impairment can significantly impact the quality of life and adherence to treatment among these patients. Further research is needed to understand the prevalence and impact of cognitive impairment in different populations and to develop effective interventions for its prevention and management.